Presentation - Giusti, Miguel; Rizo-Patrón, Rosemary (Areté, 1999)
Arete is ten years old. It is, to be sure, a modest anniversary, which nonetheless gives us the opportunity for an academic celebration. It iswith this intention that we decided, almost two years ago, to prepare a special volume dedicated to explaining, from different points of view, the notion that gives our journal its name: the notion of arete. We invited our usual collaborators and friends, and other philosophers who have dedicated part of their work to studying the origins or repercussions of that notion in the history of philosophy.